The innovation and productivity nexus in Malaysian manufacturing firms - Shafi'i, Mazlina; Ismail, Normaz Wana (Inderscience Publishers, 2015)
The study uses the Economic Census Data of 2011 to investigate the innovation-productivity nexus at firm level of Malaysia manufacturing firms. The nexus of innovation and the other determinants of productivity were examined through the augmented Cobb-Douglas production function and the outcomes were as expected. The major findings of the study confirmed that innovation plays a significant role in enhancing productivity in the manufacturing sector. Other than innovation, capital intensity, labour quality, foreign direct investment, and export are among the factors that contribute to higher productivity.